Understanding biological invasions through the lens of environmental niches - Liu, Chunlong; Bellard, Céline; Jeschke, Jonathan M. (Trends in ecology & evolution (Amsterdam), 2025)
The concept of the environmental niche is crucial in identifying mechanisms underlying successful invasions and predicting future invasions.By reconciling ecological and evolutionary factors that have previously been studied separately, the environmental niche can associate characteristics of non-native species with the possibility of species successfully invading and causing impact.The environmental niche can help to better understand inter- and intraspecific differences in invasion success, and the position of populations within the niche space is insightful in explaining the substantial variability among populations.We present a framework that combines two key concepts, the environmental niche and the invasion process, and show how existing studies assessed invasion success and impacts through the lens of environmental niches. Understanding successful invasions across taxa and systems in a unified framework is a central goal of biological conservation. While the environmental niche is a promising concept to improve our understanding of biological invasions, existing studies have not applied it to comprehensively examine all invasion stages. Here, we provide a framework that integrates the environmental niche and invasion process at both the species and the population level. By elucidating how species and populations perform in the niche space, we demonstrate how different dimensions of species niches can help in understanding inter- and intraspecific variations in the success and impact of non-native species, and identify knowledge gaps. The niche framework also offers flexibility in integrating other factors driving the success and impact of non-native species. Understanding successful invasions across taxa and systems in a unified framework is a central goal of biological conservation. While the environmental niche is a promising concept to improve our understanding of biological invasions, existing studies have not applied it to comprehensively examine all invasion stages. Here, we provide a framework that integrates the environmental niche and invasion process at both the species and the population level. By elucidating how species and populations perform in the niche space, we demonstrate how different dimensions of species niches can help in understanding inter- and intraspecific variations in the success and impact of non-native species, and identify knowledge gaps. The niche framework also offers flexibility in integrating other factors driving the success and impact of non-native species.